1976
DOI: 10.1080/03014467600001601
|View full text |Cite
|
Sign up to set email alerts
|

Age of onset of puberty in urban Argentinian children

Abstract: A cross-sectional study in La Plata city, Argentina yielded mean ages of onset of breast and pubic hair developments in 504 girls and of genitalia development in 498 boys of 10.8, 11.0 and 11.8 years respectively. These values are close to those reported previously for various other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
1
6
0
3
Order By: Relevance
“…It has been reported that somatotropin deficiency is associated with delayed onset of sexual maturation [4,11]. In our group of patients who developed spontaneously, the onset of puberty was delayed by an average of 3.2 years compared to normal Argentinian children [12] and 3.4 years compared to British children [13]. In patients who develop spontaneously, once puberty starts, it follows the same pattern as in normal boys.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been reported that somatotropin deficiency is associated with delayed onset of sexual maturation [4,11]. In our group of patients who developed spontaneously, the onset of puberty was delayed by an average of 3.2 years compared to normal Argentinian children [12] and 3.4 years compared to British children [13]. In patients who develop spontaneously, once puberty starts, it follows the same pattern as in normal boys.…”
Section: Discussionsupporting
confidence: 70%
“…Two of them attained an incomplete degree of sexual development. The mean age for the onset of spontaneous puberty was 14.99 + 1.11 (Table 2), delayed when compared to the mean of 11.8 • 1.44 years in a group of normal Argentin• children [12].…”
Section: Initiation Of Sexual Developmentmentioning
confidence: 94%
“…According to Ferguson-Smith (1965) spontaneous menses occurred in only 8o7o of patients with 45X karyotype and in 17-21°70 of those with mosaicism. In our girls with spontaneous menarche, puberty and menarche started 1 year later than normal girls in Argentina (Lejarraga et al 1976). We found a small, although non-significant, difference in final height in favour of spontaneous menarche patients: 139.2 versus 137-9 for the total sample.…”
Section: Discussionmentioning
confidence: 87%
“…The onset of spontaneous puberty in these patients took place at a mean age of ll.8SD 1-Tyears (range 9.6-14-0years) and menarche occurred at 13.6SD 1.5years (range 11-16.1 years). Both pubertal events were 1 year delayed with regard to the Argentine normal population values (Lejarraga, Castro andCuminsky 1976, Lejarraga, Sanchirico andCusminsky 1980). Two of these 17 patients had a karyotype Ann Hum Biol Downloaded from informahealthcare.com by QUT Queensland University of Tech on 11/01/14…”
Section: Resultsmentioning
confidence: 92%
“…In a previous study carried out in the same city (Lejarraga and Cusminsky 1976), it was shown that the age of onset of puberty in local middle-class children is in about the middle of the range of.world variability. Hence, there is a contrast between age of onset of puberty and age ofmenarche, when local figures are compared to world variation.…”
Section: Resultsmentioning
confidence: 96%